Hepatitis C virus genotype diversity and distribution among methadone maintenance treatment patients in Jiangsu, China. (1st January 2019) - Lu, Jing; Zhang, Li; Xu, Xiaoqin; Chen, Yuanfang; Zhou, Ying; Zhang, Zhi; Fu, Gengfeng; Chen, Guohong
Highlights: Heroin users were vulnerable for HCV infection with high seroprevalence. The distribution of HCV subtypes among heroin users in Jiangsu was complex. The geographic feature shown the dominant HCV subtype was different in six regions. There is a need for controlling the ongoing HCV epidemic in heroin users. Abstract: Background: Heroin users are vulnerable and represent a highly-infected reservoir for hepatitis C virus (HCV) infection. This study investigated HCV prevalence and genotypes distribution among heroin users who received methadone maintenance treatment (MMT) in Jiangsu. Methods: From June to December in 2016, a total of 534 patients among nine MMT clinics in six regions of Jiangsu were enrolled, with their demographic characteristics collected and serum samples tested for HCV antibody. 395 samples were seropositive and furthered to RNA extraction. HCV NS5B region fragments were amplified and subsequently sequenced. Results: Among HCV seropositive samples, 240 were characterized by NS5B partial sequences and classified into four genotypes (GPs) and eight subtypes. HCV GP3 predominated and accounted for 66.3%, followed by GP1 (27.5%), GP6 (4.2%) and GP2 (2.1%). HCV subtypes 3b (41.7%) and 3a (24.6%) were the most common subtypes. None of the demographic characteristics showed a significant difference when comparing with HCV genotypes. The geographic feature shown GPs in six regions were the same, but the frequency of subtypes exhibited regional divergence. Phylogenetic analyses demonstrated that 3b had become a local endemic in Jiangsu. Conclusion: The distribution of HCV subtypes among heroin users in Jiangsu province was complex. The data could provide more precise estimates for HCV prevalence and genotype distribution as well as heroin users of Jiangsu province.